Topological modular forms - Douglas, C; Francis, J; Henriques, A; Hill, M (American Mathematical Society, 2014)
DEFINITION 3.5. An integral modular form of weight n is a law associating to every pointed curve of genus 1 a section of wo" in a way compatible with base change. From the discussion above, examples of integral modular forms of weight 4, 6, ...